2017
DOI: 10.1002/ppsc.201700222
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide Nanoparticles with Visible and Near-Infrared Autofluorescence

Abstract: Nowadays, self‐fluorescent materials such as quantum dots are widely studied and applied in biomedical field. However, the biggest obstacle is biocompatibility. Here, a novel autofluorescent nanoparticle is constructed by crosslinking polyacrylamide nanoparticles (PAANPs) that contain ε‐poly‐l‐lysine with glutaraldehyde (named fPAANPs). The nanoparticle has a mean size of about 16 nm, a zeta potential of about +16 mV, and strong visible and near‐infrared autofluorescence. The nanoparticle can be efficiently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…In addition, due to the use of APMA and ε-PL, PAMNPs had positive charges. Our study also demonstrated that PAMNPs had high biocompatibility in vitro and in vivo …”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, due to the use of APMA and ε-PL, PAMNPs had positive charges. Our study also demonstrated that PAMNPs had high biocompatibility in vitro and in vivo …”
Section: Introductionsupporting
confidence: 72%
“…The surface properties of polyacrylamide nanoparticles (PAMNPs) can be modified through introducing functional reactive groups by adding different monomers during the preparation process such as introducing the carboxyl groups by adding acrylic acid monomer and introducing the amino groups by adding APMA . We have previously synthesized a kind of PAMNP with autofluorescence of both visible fluorescence (VF) and near-infrared fluorescence (NIRF) . This kind of autofluorescence is generated by glutaraldehyde (GTA) cross-linking, which produces two different double bonds, CN and CC .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polyacrylamide, a hydrophilic polymer, was selected because of its biocompatibility and low toxicity . Polyacrylamide nanobeads have been used for a wide array of biomedical applications ranging from imaging and MRI contrast to photodynamic therapy because they are amenable to the addition of fluorophores, photosensitizers, or to encapsulate magnetic iron oxide nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…In functional analyses of interactions between microbes such as endophytes and roots, the labeling of bacteria with fluorescent proteins or application of transcriptional fusions with reporter genes to visualize and measure bacterial gene expression is very common (Buschart et al ., 2012; Chen et al ., 2015; Sarkar et al ., 2017). For fluorescent staining, the signal may be enhanced by increasing the amount of the fluorescent dye and eliminating the autofluorescence by irradiation with light before staining (Neumann & Gabel, 2002), or by treating the sample with some autofluorescence reducing agent (Xie et al ., 2017). However, for in vivo studies applying fluorescent proteins, the autofluorescence is problematic, especially when the fluorescent protein is not strongly expressed.…”
Section: Introductionmentioning
confidence: 99%